Critical Evaluation for Education Reform - Waters, Gisele A. (Education Policy Analysis Archives, 1998)
The school reform movement has done little to provide an accurate analysis of the production of inequality or the reproduction of social injustice in the public schools or the larger social order. The ideology that influences this movement has often prevented the realization of any notion of an egalitarian ideal, the elimination of inequality, or the improvement of those who are least well-off. I ask educators and evaluators of education reform efforts to reconsider critically their roles in social science research, to reclaim the battleground of public school reform by focusing on the democratic purpose of public schooling, and the institutional problems in educational programs and practice that often inhibit action toward this ideal. The first part of this article includes an extensive argument explaining the "why" of critical evaluation. The theoretical literature on inquiry in science and social science, the ideology of critical theory, critical social psychology, and Freirean pedagogy are consulted as additional tools for augmenting the practice, policies, and responsibilities of evaluators in education. I review three contemporary perspectives of evaluation in order to begin rethinking the purposes and functions that evaluation serves in education. It also demonstrates how mainstream and contemporary evaluations can be used to serve a particular set of social and political values. The second part of this article begins a preliminary journey toward describing the "how" of critical evaluation. Critical evaluators can fight for social justice by combining the merit criteria of state and federal public education law, and the methods of an adversary oriented evaluation in order to transform educational environments that serve the future potentials of all children. Therefore education involves the practice of freedom, the means by which men and women deal critically and creatively with reality and discover how to participate in the transformation of their world (Freire, 1985).